1995
DOI: 10.1093/ajcn/62.6.1322s
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among vitamin C, vitamin E, and beta-carotene

Abstract: The effects of vitamin C (ascorbic acid), vitamin E (alpha-tocopherol), and beta-carotene as antioxidants and their cooperative action against the oxidation of lipid in solution, membranes, and lipoproteins have been studied and reviewed. Ascorbic acid and alpha-tocopherol act as potent, and probably the most important, hydrophilic and lipophilic antioxidants, respectively. They function at their own site individually and furthermore act synergistically. beta-Carotene has lower reactivity toward radicals than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
206
2
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(224 citation statements)
references
References 28 publications
7
206
2
9
Order By: Relevance
“…Davies and Timmins [46] showed rate constant reactions of <10 5 dm 3 mol −1 s −1 and 1.3× 10 7 dm 3 mol −1 s −1 for the interactions of α-tocopherol and ascorbic acid respectively with the L· radical. In addition, Niki et al [47] suggested that α-tocopherol cannot stabilise the alkoxyl radical before attacking polyunsaturated fatty acids, as the reaction rate constant for this interaction is relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…Davies and Timmins [46] showed rate constant reactions of <10 5 dm 3 mol −1 s −1 and 1.3× 10 7 dm 3 mol −1 s −1 for the interactions of α-tocopherol and ascorbic acid respectively with the L· radical. In addition, Niki et al [47] suggested that α-tocopherol cannot stabilise the alkoxyl radical before attacking polyunsaturated fatty acids, as the reaction rate constant for this interaction is relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that beta carotene is found only in trace amounts in the retina (25)(26)(27)(28) provides some indirect support for this possibility. Nevertheless, a possible indirect effect of beta carotene in the AREDS formulation, mediated through interaction with other trial ingredients (29)(30)(31), cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate can also recycle vitamin E, or α-tocopherol, from its radical form (Niki et al, 1995). The importance of ascorbate recycling of α-tocopherol stems from properties of the latter as a lipophilic antioxidant, capable of interfering with atherogenic oxidative modification of LDL (Esterbauer et al, 1990;Thomas & Stocker, 2000).…”
Section: Ascorbate Dietary Requirements and Functionmentioning
confidence: 99%
“…This cooperative relationship has been shown to significantly decrease copper mediated LDL oxidation in vitro (Berliner & Heinecke, 1996;Esterbauer et al, 1990), down regulate expression of endothelial VEGF Rodriguez et al, 2005), and decrease production of reactive oxygen species though down regulation of vascular NADPH oxidase (Chen et al, 2001). While there is ample in vitro evidence that ascorbate spares α-tocopherol in plasma LDL (Frei et al, 1989;Niki et al, 1995), results are mixed as to whether ascorbate protects it in cells. Glascott and co-workers (Glascott, Jr. et al, 1996) found that there was no sparing of α-tocopherol by ascorbate in hepatocytes exposed to an oxidant stress generated by allyl alcohol.…”
Section: Ascorbate Dietary Requirements and Functionmentioning
confidence: 99%
See 1 more Smart Citation